An improved DNA extraction method and standardisation of transmission studies of enation leaf curl virus in okra (Abelmoschus esculentus) - NISHANT; SHARMA, SUSHEEL KUMAR; DIKSHA, DAMINI; NAIK, RESHAV; NIRANKAR; YADAV, RAMESH KUMAR (The Indian Journal of Agricultural Sciences, 2026)
In India, okra (Abelmoschus esculentus L.) is severely affected by OELCuV (Okra enation leaf curl virus) which is influenced by vector (white fly, Bemisia tabaci), host and environment. DNA isolation from Malvaceae plant families is difficult due to high mucilage content, which binds to secondary metabolites and interferes with molecular studies. The study was carried out during 2023–2024 at ICAR-Indian Agricultural Research Institute, New Delhi to utilise a supplemented extraction buffer with 2.0 g of polyvinylpyrrolidone (PVP) per 50 mL to neutralise polyphenols. The samples were treated with chloroform: isoamyl alcohol (24:1) twice for effective phase separation and mucilage removal. Additionally, a washing step with 10 mM ammonium acetate was incorporated to eliminate residual polysaccharides and proteins, enhancing DNA purity. This protocol yielded high quality DNA with an average concentration of 1501.35 ng/μL and purity ratios of A260/A280 = 1.82 and A260/A230 = 1.78, outperforming commercial kits and conventional methods of DNA isolation. Using a controlled whitefly culture, the study assessed Begomovirus abelmoschusenation transmission efficiency across various okra seedling growth stages. Virus acquisition and inoculation required minimum access periods of 45 min, with transmission efficiency increasing over time and vector density. Maximum transmission (100%) was observed at 24 h after acquisition and inoculation access periods using 12 whiteflies/seedling. Younger seedlings (10–12 days old) exhibited the highest susceptibility, while no transmission occurred in plants older than 45 days. Furthermore, PCR analysis confirmed the absence of seed transmission. The study offered key insights into Begomovirus abelmoschusenation epidemiology and improved okra viral disease diagnostics and management.